A scientific educational activity of the Doctor of church law Alexander Ivanovych Pokrovskiy - Єфремова, Наталя Володимирівна; Єфремова, Н. В.; Ефремова, Наталья Владимировна; Yefremova, Natalia V.; Горяга, Оксана Вікторівна; Горяга, О. В.; Горяга, Оксана Викторовна; Horiaha, Oksana V.; Півень, Дмитро Олегович; Півень, Д. О.; Пивень, Дмитрий Олегович; Piven, Dmytro O. (Universidad de la Amazonia, 2020)
Аmongthe different branches of law, theChurch Law of the Eastern Orthodox Church is a holistic law system and a comprehensive branch of knowledge, which unites the judicial, historical and theological studies elements. Unfortunately, in Soviet times Church Law as a science and as a subject hadbeen deleted from the programs of the law faculties. Even at the renewed seminaries it showed up only at the end of the XX century.However, the Church Law has close ties with a law culture, spiritual heritage and national traditions of the Ukrainian people, because it is an important source of the national law system. The resumption of research interest, therefore, in the history of the Church Law teaching has shown by the most modern Ukrainian researchers as one of the relevant targets of the national law science development.In this article, the history of appearance and development of Church Law Faculty at the Imperial NovorossiyskUniversity is investigated. The article focuses on the activity of Professor A. I. Pokrovskiy, who was the last specialist of this subject at the University. Once in Odesa in 1917, he worked productively at the improvement of the church law teaching, but with the beginning of the Bolshevik terror, he was forced to survive in the conditions of implementation of the destructive reforms in the education sector in USSR. The collected materials will promote renewing the pages of his scientific-educational activity and allow us to know about the important stages of his life and his scientific achievements.

Серед різних галузей права Церковне право Східної Православної Церкви - це цілісна правова система та всебічна галузь знань, яка об'єднує елементи судових, історичних та богословських досліджень. На жаль, за радянських часів церковне право як наука і як предмет було вилучене з програм юридичних факультетів. Навіть у оновлених семінаріях він з'явився лише наприкінці XX століття. Однак церковне право тісно пов'язане з правовою культурою, духовною спадщиною та національними традиціями українського народу, оскільки є важливим джерелом національної правової системи. Тому відновлення науково-дослідницького інтересу в історії викладання церковного права найсучаснішими українськими дослідниками є однією із релевантних цілей розвитку національної юридичної науки. У цій статті досліджується історія появи та розвитку церковного юридичного факультету Імператорського Новоросійського університету. Стаття присвячена діяльності професора О. І. Покровського, який був останнім фахівцем з цього предмету в університеті. Опинившись в Одесі в 1917 році, він продуктивно працював над вдосконаленням викладання церковного права, але з початком більшовицького терору він був змушений пережити здійснення деструктивних реформ у сфері освіти в СРСР. Зібрані матеріали сприятимуть оновленню сторінок його науково-освітньої діяльності та дозволять нам дізнатися про важливі етапи його життя та його наукові досягнення.
Yefremova N. A scientific educational activity of the Doctor of church law Alexander Ivanovych Pokrovskiy / N. Yefremova, О. Horiaha, D. Piven // Amazonia Investiga. - Vol. 9. - Issue 28. - Universidad de la Amazonia, 2020. - P. 225-233.
Keywords: A. I. Pokrovskiy; Church Law; Canon Law; Novorossiysk Imperial University; О. І. Покровський; церковне право; канонічне право; Новоросійський імператорський університет; Research Subject Categories::HUMANITIES and RELIGION